Evaporation-driven thermocapillary Marangoni convection in liquid layers of different depths. (July 2018) - Sankaran, A.; Yarin, A.L.
Graphical abstract: Highlights: Infrared measurement of surface temperature of evaporating ethanol layer. Measurements at room temperature and with heating from the bottom. Tracking light particle motion due to Marangoni convection at the free surface. Theoretical model which employs the Goursat potentials technique. Abstract: In the experimental part, which employed infrared (IR) camera, temperature distributions at the free surface of ethanol layers in deep and shallow vessels under room temperature or subjected to heating from below in the 68–105 °C temperature range (including the ethanol boiling temperature of 78.3 °C) were studied, and correlated with the heater surface temperature. The regular and irregular Marangoni convection patterns were recognized. Light particles fully entrained by the Marangoni convection on the free surface were tracked and their velocities were measured and compared to the theoretical predictions. Namely, a model was developed for the Marangoni-driven convection due to a non-uniform evaporation-related cooling of the free surface of a liquid in an open vessel. In this case, an analytical solution of the plane problem in the creeping flow approximation was found using the general Goursat solution of the biharmonic equation for the stream function and the complex potential technique of Kolosov and Muskhelishvili. The velocity of thermocapillarity-driven motion of tiny particles toward the cooler center was predicted and found to be in reasonable agreement with the experimental result.